Revisiting the Newly Modified Criteria for Arrhythmogenic Right Ventricular Cardiomyopathy/Dysplasia (ARVC/D) and Reporting Newly Identified Genes. (2nd November 2022) - Chang, Eric; Daboul, Rania; Hanan, Abdul; Abdo, Mena; Poulik, Janet; Eskarous, Hany; Hadjilambris, Anna Maria; Shehata, Bahig M.
Abstract: Background: Arrhythmogenic Right Ventricular Cardiomyopathy/Dysplasia is an inherited cardiomyopathy, characterized by replacement of the RV muscle wall with fibrofatty tissue. The diagnosis is challenging, due to the absence of a unique presentation and a lack of specific reproducible diagnostic criteria. Materials and methods: Slides and additional clinical information including follow up from 16 cases were reviewed. Pediatric criteria of >30% of muscle replacement was used, instead of >40% as used in adults. Results: All 16 cases were confirmed by genetic testing and show ARVC/D. Applying the adult criteria, 7 cases would not have been categorized as ARVC/D. Conclusion : The modified pediatric criteria for ARVC/D should be used for pediatric patients. Better detection will aid in genetic counseling in order to identify those additional family members susceptible to sudden cardiac deaths so they can be followed optimally.